Al-Maṣlaḥah al-Mursalah sebagai Sumber Hukum (Studi Analisis Pendapat al-Syāfi’ī dalam Kitab al-Risālah) - Rahmayani Rahmayani; Muttazimah Muttazimah; Nuraisyah Syahrun (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
Many classical and contemporary scholars use al-Maṣlaḥah al-mursalah as a source or method of adopting Islamic law on issues that have not been explained in detail in the texts, whether in the Al-Qur'an or hadith. The aim of the research is to find out the views of Imam al -Syāfi'ī regarding the position of al-maṣlaḥah al- mursalah as a source of law and his opinion about al-maṣlaḥah al-murlah as a source of law in the book al-Risālah. The formulation of the problem raised is; First, what is Imam al-Syāfi'ī's view regarding the position of al-maṣlaḥah al-mursalah as a source of law. Second, what is Imam al-Syāfi'ī's opinion in the book al-Risālah regarding al-maṣlaḥah al-mursalah as a source of law. Researchers use qualitative research with library research methods which focus on the study of manuscripts and texts, using normative and conceptual approach methods. The results can be concluded as follows; Firstly, Iman al-Syāfi'ī does not reject al-maṣlaḥah al-mursalah absolutely, but he considers that the use of this method must be based on several conditions. This opinion is strengthened by the opinion of the scholars of the Second Syāfi'ī school, the results of the researcher's analysis of al-maṣlaḥah al-mursalah as a source of law in the book al-Risālah, that Imam al-Syāfi'ī does not mention the rejection or permissibility of blaspheming with methods or sources the. It is hoped that the implications of this research will be a reference for a mujtahid when he wants to establish a law using the al-maṣlaḥah al-murlah method.